Assessment of walkability through objective measurement and pedestrian perception a comparative study of the major city centers in Mindanao - Tilendo, Mia Fatima I. (2019)
This study is conducted to primarily assess the walkability condition of the four major city centers in Mindanao. The researcher utilized both quantitative and qualitative approach in the study. As a part of quantitative analysis, the researcher assessed the physical and environmental condition of the city centers using the Macro Scale Assessment Base Model developed by de Cambra (2012) which includes the attractiveness and accessibility of the built environment. In the qualitative approach in the study, the researcher assessed the built environment using the Pedestrian Perception Survey conducted to 100 respondents each city. Finally, a descriptive correlation analysis was used in comparing the result of the two techniques (quantitative and qualitative measurement). Analysis shows that Davao City, specifically San Pedro Street, has scored 92.7%, the highest in terms of its walkability. Proper balance of attractiveness and accessibility of the built environment with its components (Connectivity, Convenience, Comfort, Conviviality, Coexistence, and Commitment) are essential to have a more pedestrian-friendly environment. In conclusion, the built Environment has a vital role in influencing people to walk. The cities being assessed have the opportunity to positively contribute to society not only by following existing sustainability principles, but also by paving the way for more innovative, sustainable, and healthier architectural practices. Lastly, this study proposed a Town Center Development with a high walkability score in Davao City. It was incorporated with valuable architectural concepts and guidelines in designing a pedestrian-friendly development to address the existing problems based on the analysis and results of the study.